Paralegal Village Legitimacy in Providing Access to Justice Through Legal Assistance - Gede Agung Wirawan Nusantara; I Made Aditya Mantara Putra (Community Service Journal of Law, 2022)
Legal aid is a citizen's right and legal obligation for the state as regulated in international legal instruments and national legal instruments. In the distribution of legal aid, the idea of a village paralegal was born. One of the ways to fulfill this access to justice is by optimizing the role of paralegals at the village level. Village paralegals are expected to help the community in the village understand the law. In this study, two problems were discussed, namely regarding the position of paralegals in fulfilling the right to legal aid and the function of village paralegals in solving legal problems. The provision of legal aid aims to provide access to justice, equity and fulfillment of civil rights and political rights of all people. Paralegals have the task of providing legal assistance to the poor as a form of service for the poor who need assistance in obtaining their legal rights. The formation of village paralegals is very important to overcome legal problems that exist at the village level. Handling conflict in the village is not enough with a social and cultural approach but also with a legal approach.